Cover Picture: Nitrogen Analogues of o‐Quinodimethane with Unexpected non‐Kekulé Diradical Character (Chin. J. Chem. 6/2018). Issue 6 (14th May 2018) - Li, Tao; Cheng, Cheng; Yuan, Ningning; Wang, Lei; Chen, Chao; Tan, Gengwen; Wang, Xinping
Abstract : The cover picture shows   para ‐Quinodimethane ( p ‐QDM) and ortho ‐quinodimethane ( o ‐QDM) are two typical examples of Kekulé‐type delocalized diradicals. The cover picture shows that the replacement of the carbinyl centers with isoelectronic aminium centers leads to the formation of isolable nitrogen analogues of o ‐QDM. In contrast to o ‐QDM, the nitrogen analogues exhibit unexpected non‐Kekulé diradical characters and features open‐shell singlet ground states with thermally accessible triplet states. More details are discussed in the article by wang et al. on page 487–490. Abstract : The cover picture shows   para ‐Quinodimethane ( p ‐QDM) and ortho ‐quinodimethane ( o ‐QDM) are two typical examples of Kekulé‐type delocalized diradicals. The cover picture shows that the replacement of the carbinyl centers with isoelectronic aminium centers leads to the formation of isolable nitrogen analogues of o ‐QDM. In contrast to o ‐QDM, the nitrogen analogues exhibit unexpected non‐Kekulé diradical characters and features open‐shell singlet ground states with thermally accessible triplet states. More details are discussed in the article by wang et al. on page 487–490.